Reading the road, from Shakespeare's crossways to Bunyan's highways - Hopkins, Lisa, 1962-; Angus, Bill (Edinburgh University Press, 2020)
This book brings together thirteen essays, by both established and emerging scholars, which examine the most influential meanings of roads in early modern literature and culture